Mikrodalga Yardımı İle Yeni Ftalosiyaninlerin Sentezi - Zengin, Hilal (Fen Bilimleri Enstitüsü, 2013)
Ftalosiyanin kelimesi, “nafta (kaya yağı)” ve “siyanin (koyu mavi)” sözcüklerinin Yunanca karşılıklarından türetilmiştir. “Ftalosiyanin” (Pc) ismi ilk kez 1933 yılında Imperial Bilim ve Teknoloji Kolejinde çalışan Profesör Reginald P. Linstead tarafından metalsiz ve metalli ftalosiyaninler ile bunların türevlerinden oluşan organik bileşikler sınıfını tanımlamak için kullanılmıştır. Ftalosiyanin, 18-π elektron sistemine sahip düzlemsel ve tam aromatik bir makrohalkadır. Ftalosiyanin molekülünün merkezi, kompleks oluşumuna doğrudan katılan dört adet azot atomu ile iki imino hidrojen atomundan oluşur. Periyodik tablonun hemen hemen tüm metal iyonları ile koordine edilebilme yeteneğine sahiptir. Bu, makromolekülün çok farklı özelliklere sahip olmasını sağlar. Ayrıca aromatik bileşiklerde kolaylıkla gerçekleşebilen elektrofilik ve nükleofilik sübstitüsyon tepkimelerinin ftalosiyaninlere de uyarlanabilmesi göz önüne alındığında, oldukça fazla sayıda bileşiğin kolaylıkla hazırlanabileceği görülmektedir. Makrohalka bileşiklerinin önemli bir sınıfı olan ftalosiyaninler kimyasallara ve ısıya karşı yüksek kararlılık göstermeleri ve sahip oldukları fiziksel ve kimyasal özellikleri bakımından çok değerli yapılardır. Çeşitli yapılardaki ftalosiyaninlerin sentezi uygulama alanlarının genişletilmesine fırsat sunmmaktadır. Ftalosiyanin türevleri elektrofotografi, optik veri toplaması, gaz sensörü, sıvı kristal, lazer teknolojisi için boyar madde olarak kullanımı gibi pek çok uygulama alanına sahiptir. Ftalosiyaninlerin çözünürlükleri uygulama alanlarının belirlenmesinde etkileyici faktördür. Özellikle kanserin fotodinamik tedavisi için suda çözünür ftalosiyaninlere ihtiyaç duyulmaktadır. Bu çalışmada periferal konumda 2-{[2(Dimetilamino)etil]-metilamino}etoksi grubuna sahip tetra sübstitüe ftalosiyanin türevleri sentezlenilmesi ve (4-{[2(dimetilamino)etil]-metilamino}etoksi) ftalonitrilin kuaternize edilerek, bu ftalonitril türevinden suda çözünür okta katyonik kuaternize Zn ftalosiyanin elde edilmesi amaçlanmıştır. Sentezlenen bu yeni bileşiklerin yapıları, 1HNMR, IR ve UV-vis teknikleri kullanılarak aydınlatılmıştır. Çalışmanın ilk kısmında 4-nitro ftalonitril ile 2-{[2(dimetilamino)etil] metilamino}etanol kuru DMSO içerisinde azot atmosferi altında susuz potasyum karbonat (K2CO3) varlığında 35°C’ deki nükleofilik sübstitusyon reaksiyonu sonucunda 4-{[2(dimetilamino)etil] metilamino}etoksi ftalonitril (1) bileşiği elde edilir. Sentezlenen ftalonitril türevi kloroform, THF, DMF ve aseton da çözünmektedir. Sentezlenen dinitril türevinin (1) IR spektrumunda 2230 cm-1’de C≡N gruplarına ait gerilme titreşimleri, 2945-2770 cm-1 aralığında alifatik C-H gerilme titreşimleri ve 1258 cm-1’de de C-O-C gruplarına ait gerilme titreşimleri gözlenmiştir. 1 bileşiğinin CDCl3 içinde alınan 1H-NMR spektrumu incelendiğinde aromatik protonlar 7.68-7.17 ppm arasında, -CH2-O-Ar grubundaki protonlar 4.12 ppm de, -CH2-N- grubundaki alifatik protonlar 2.38, 2.55 ve 2.83 ppm de, CH3 (6H) grubundaki protonlar 2.31 ppm de ve CH3 (3H) grubundaki protonlar 2.20 ppm de yapıyı destekleyecek şekilde gözlemlenmiştir. Çalışmanın ikinci kısmında 1 bileşiğinin siklotetramerizasyonu ile tetra sübstitüe Zn(II), Co(II) ve Mn(II) ftalosiyanin türevleri 2, 3 ve 4 sentezlenmiştir. Sentezlenen ftalonitrilin (1) uygun metal tuzları (Zn(CH3COO)2, CoCl2 ve MnCl2) ile DMAE varlığında mikrodalga enerjisine maruz bırakılarak 140oC’de reaksiyonu gerçekleştirilerek hedeflenen Zn(II)Pc (2), Co(II)Pc (3) ve Mn(III)Pc (4) elde edilmiştir. Ftalosiyanin sentezinde ftalonitril türevindeki C≡N gruplarına ait gerilim piklerinin kaybolması ftalosiyaninlerin oluştuğunu göstermektedir. Çinko ftalosiyanin (2) bileşiğinin IR spektrumunda 2930 ve 2857 cm-1’ de alifatik C-H gerilme titreşimleri gözlenmiştir. Bu bileşiğin CHCl3 içerisinde alınan UV-Vis spekrumunda 350 nm’de B bandına, 678 nm’de ise Q bandına ait pikler gözlenmiştir. Çinko ftalosiyanin bileşiğinin CDCl3 içerisinde alınan 1H-NMR spektrumda aromatik protonlar 7.55-6.91 ppm aralığında, CH3 (24H) grubundaki protonlar 2.21 ppm’de ve CH3 (12H) gruplarındaki protonlar 2.33 ppm’ de, -CH2-O-Ar grubundaki protonlar 4.12 ppm de, -CH2-N grubundaki protonlar ise sırasıyla 2.55 ve 3.49 ppm de gözlenmiştir. Kobalt ftalosiyanin (3) bileşiğinin IR spektrumunda 2931 ve 2866 cm-1 de alifatik C-H gerilme titreşimleri gözlenmiştir. Bu bileşiğin CHCl3 içerisinde alınan UV-Vis spekrumunda 331 nm’de B bandına, 677 nm’de ise Q bandına ait pikler gözlenmiştir. Mangan ftalosiyanin (4) bileşiğinin IR spektrumunda 2938 cm-1 de alifatik C-H gerilme titreşimleri gözlenmiştir. Bu bileşiğin DMSO içerisinde alınan UV-Vis spekrumunda sırasıyla 370, 502, 736 nm’de absorbsiyon pikleri gözlenmiştir. Çalışmada daha sonra sentezlenen ligand (1) kloroform içerisinde aşırı metiliyodür eklenerek 12 saatte ve oda sıcaklığında kuaternize edilmiştir. Kuaterzie ftalonitril türevi su, DMSO ve etanolde çözünürlük özelliğine sahiptir. Kuaternize ftalonitril türevi (5) bileşiğinin IR spektrumunda 2234 cm-1’ de C≡N gruplarına ait gerilme titreşimleri, 3085 cm-1 de aromatik C-H ve 2900 cm-1‘ de alifatik C-H gerilme titreşimleri gözlenmiştir. Son olarak kuaterner ligand (5), dimetilaminoetanol varlığında Zn(CH3COO)2 ile mikrodalga enerjisi yardımıyla 140oC reaksiyona girerek kuaterner çinko ftalosiyanin (6) elde edilmiştir. Elde edilen QZnPc su, DMF, DMSO ve etanolde çözünmektedir. Kuaternize ZnPc (6) bileşiğinin IR spektrumunda 2953 cm-1 aralığında alifatik C-H gerilme titreşimleri gözlenmiştir. Bu bileşiğin d-DMSO içerisinde alınan 1H-NMR spektrumda aromatik protonlar 8.04-7.46 ppm aralığında, -N-CH3 (36H) gruplarındaki protonlar 3.17 ppm ve -N-CH3 (12H) gruplarındaki protonlar 3.26 ppm de gözlenmiştir. -CH2-O-Ar grubundaki protonlar 5.23 ppm’ de, -CH2-N- grubundaki alifatik protonlar sırasıyla 3.41 ve 3.82 ppm de ve –O-CH2 deki protonlar 5.23 ppm’de gözlemlennmiştir. Bu bileşiğin DMSO içerisinde alınan UV-Vis spekrumunda B ve Q bandları sırasıyla 299 ve 683 nm’de absorbsiyon pikleri gözlemlenmiştir. gözlenmiştir. Sonuç olarak yapılan bu çalışmada farklı metaller içeren ftalosiyanin türevleri sentezlenmiş ve spektroskopik özellikleri incelenmiştir.

The word phthalocyanine is derived from the Greek for naphtha (rock oil) and cyanine (blue). It was first used by Linstead in 1933 to describe a new class of organic compounds consist of metal free and metallo phthalocyanine derivatives. Phthalocyanine is a planar and aromatic macrocycle complexes having 18- π electronic system. The central part of the molecule consists of four nitrogens directly involving complexation, and two imino hydrogens. The core is capable of coordinating almost all metal ions and this in turn enables the macrocycle to have a broad spectrum of properties. If it is considered that electrophilic and nucleophilic substitution reactions can easily be applied to aromatic systems, phthalocyanines will also have a great range of substitution opportunities. Phtalocyanines are able to entrap more than 70 metal and ametal cations inside their innerring spaces. Furthermore, it is possible to bind a variety of substitue mixture, which changes electronic structure of the system, to macrocyclic molecule. These groups can improve Pc s solubility Phthalocyanines (Pcs) are an important class of aromatic macrocycles with high chemical and thermal stability that possess unique physical and chemical properties. Synthesis of phthalocyanines derivatives gives opportunities to develop their applications in various fields such as chemical sensors, liquid crystals, second generation photosensitizers for photodynamic therapy, optical limiting devices and non-linear optics. The solubility of Pcs is significant property for moderating their physical and chemical properties and optimizing their performance for their applications in many fields; especially their water solubility has a strong effect in order to be used phthalocyanines as photosensitizier for photodynamic theraphy (PDT) of cancer. PDT is an alternative method in the treatment of cancer thearapy. Traditional cancer therapies like chemotherapy give rise to serious problems because of death of healthy cells. PDT requires three fundemental factors that are oxygen, light and photosensitizier. Also water solubility of phthalocyanine derivatives is an important factor to be ideal photosensitizer. The quaternizied phthalocyanine complexes shows good solubility in some organic and aqueous solution, in this way they are used as potential photosensitizier for PDT. In this work, it is aimed to synthesize and characterize 2-{[2(dimethylamino)ethyl]-methylamino}ethoxy sübstitüed metallo phthalocyanines in periferal position and water soluble octa cationic Zn(II) phthalocyanine. All these new compounds were characterized by 1H-NMR, UV/Vis and IR spectroscopy. In the first part of this work, we synthesized 4-{[2(dimethylamino)ethyl]-methylamino}ethoxy phthalonitrile (1) from the nucleophilic substitution reaction of 4-nitrophthalonitrile and 2-{[2(dimethylamino)ethyl]-methylamino}ethanol in the presence of K2CO3 in dry DMSO at 35 oC under nitrogen atmosphere. It is soluble in chloroform, THF, DMF and acetone. In the IR spectrum of compound 1, stretching vibrations of C≡N groups groups are appeared at 2230 cm-1 and CH of aliphatic groups are observed at 2966 and 2770 cm-1 by the intense bands. In the IR spectrum of 4-nitrophthalonitrile the absorption band corresponding to –NO2 vibrations dissappears after its conversion into the phthalonitrile derivative (1). In the 1H-NMR spectrum of compound 1, aromatic protons were observed between 7.68-7.17 ppm. Aliphatic protons of -CH2-O-Ar are appeared at around 4.12 ppm and aliphatic protons of -CH2-N- are observed at 2.38, 2.55 ve 2.83 ppm. Also protons of CH3 (6H) are placed at 2.31 ppm. These results support the formation of compound 1. In the second part of this work, periferal tetrasubstituted metallo phthalocyanines were synthesized. By utilizing of microwave irradiation, the cyclotetramerization of 2-{[2(Dimethylamino)ethyl]-methylamino}ethoxy phthalonitrile (1) in DMAE at 140 oC with corresponding metal salts (Zn(CH3COO)2, CoCl2, MnCl2) under nitrogen atmosphere resulted with the formation of metallo phthalocyanine (2). A mixture of phthalonitrile (1) and Zn(CH3COO)2 in DMAE was stirred at 140 oC for under nitrogen atmosphere by making use of MW irradiation. In the IR spectrum of Zn (II) phthalocyanine (2), stretching vibrations of aliphatic C-H group appeared at 2930 and 2857 cm-1. Cyclotetramerization of dinitrile was confirmed by the disappearance of the sharp C≡N vibration at 2230 cm-1. In the 1H NMR spectrum of compound 2 in CDCl3, the aromatic protons appear as between 7.55-6.91 ppm. Aliphatic protons of -CH2-O-Ar and -CH2-N appeared 4.12, 2.55 and 3.49. also protons of CH3 (24H) and CH3 (12H) are observed at 2.21 and 2.23 ppm. UV-Vis spectra of complex 2 and 3 in chloroform exhibited intense single Q band absorption at 678 and 677 nm respectively. B bands of these phthalocyanines appeared in the UV region at 350 and 331nm. In the IR spectrum of Co (II) phthalocyanine (3), stretching vibrations of aliphatic C-H group appeared 2931 and 2866 cm-1. UV-Vis spectra of Mn(III) phthalocyanine (4) in DMSO, shows Q band absorption at 736 nm and B band absorption at 370 nm. After that to obtain quaternized 4-{[2(Dimethylamino)ethyl]-methylamino}ethoxy phthalonitrile (5), the ligand (1) was reacted with excess of CH3I in the chloroform in the dark at room temprature. Quaternized phthalonitrile derivative is soluble in water, DMF, DMSO and slightly soluble in ethanol. In IR spectrum of complex (5), C≡N vibrations occurred 2234 cm-1, stretching C-H vibrations of aliphatic and aromatic appeared at 2234 and 3085 cm-1 respectively. At last part of this study, water soluble octa cationic Zn(II) phthalocyanine was synthesized. With the help of microwave irradiation, the cyclotetramerisation of quaternized phthalonitrile derivative (5) in DMAE at 140 oC with (Zn(CH3COO)2, under nitrogen atmosphere resulted with the formation of octa cationic ZnPc (6). It is soluble in water, DMF, DMSO and slightly soluble in ethanol. UV-Vis spectra of QZnPc (6) in DMSO, exhibited intense single Q band and B band absorption appears at 683 and 299 nm respectively. In the 1H-NMR spectrum of compound 6 in d-DMSO, aromatic protons were observed between 8.04-7.46 ppm. Protons of N-CH3 (36 H) and N-CH3 (12H) groups appeared at 3.17 and 3.26 ppm respectively. Also appeared 5.23 ppm of protons of -CH2-O-Ar and 3.41, 3.82 ppm peaks of - CH2-N- and 5.23 ppm of –O-CH2 protons are appeared. In IR spectrum of QZnPc, stretching vibrations of aliphatic CH occurred 2953 cm-1 As a result, a novel phthalonitrile derivative, its quaternized complex and corresponding metallophthalocyanines were synthesized and chracterizied in this study. The main purpose of quaternized of phthalocyanines is to obtain water soluble phthalocyanine in order to use them as photosensitier for photo dynamic therapy.
Micro-wave Assisted Synthesis Of Novel Phthalocyanines
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2013
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2013
Keywords: ftalosiyanin; phthalocyanine